STRATEGI REHABILITASI LAHAN DI DAS PADANG BERDASARKAN KESESUAIAN TEMPAT TUMBUH JENIS-JENIS POHON (LAND REHABILITATION STRATEGY IN PADANG WATERSHED BASED ON TREES SPECIES SUITABILITY MAP) - Ahmad Dany Sunandar (Badan Penelitian dan Pengembangan Provinsi Sumatera Utara, 2017)
Padang watershed is one of important watersheds to address in North Sumatra related to the biophysical and socio-economic conditions in this watershed. The problem that routinely occurs in Padang watershed is the annual floods. Degraded watershed quality could be improved by rehabilitation, especially in barren lands or biophysically need to be forested land. The objective of this research is to determine the condition of land cover in Padang watershed and develop rehabilitation strategies that need to be applied in Padang watershed based on tree species suitability map of the watershed. The method used was based on the collection of information and data suitability of tree species on the watershed unit through spatial data processing using geographic information systems (GIS). Based on spatial data processing, forested area in Padang watershed reaches 28.44% of the watershed area, but its conditions have changed with only 7.17% of the area remain as forested area or 7.932 hectares. The land tends to be potentially critical and critically injured. Map of suitability for the tree species that could be planted in the watershed Padang compiled based on the results of field surveys and recommendation types that correspond to a growing requirement in Padang watershed. As a recommendation, land use, especially in the upper Padang watershed must be returned to its function as a buffer area of watershed system especially related to agriculture / plantation, cropping patterns and land use. Keywords: rehabilitation, land suitability map, Padang watershed, forest land